2020
DOI: 10.3390/jcm9092896
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of Crohn’s Disease in Catalonia from 2011 to 2017. Increasing Use of Biologics Correlates with a Reduced Need for Surgery

Abstract: Background and Aims: Data from clinical trials suggest that biological drugs may improve the outcomes in Crohn’s disease (CD) by reducing the need for surgery or hospitalization. The aim of this study is to evaluate the time-trends of the use of biological drugs and other treatments for CD, and its relationship with outcomes in Catalonia. Materials and Methods: All patients with CD included in the Catalan Health Surveillance System (containing data on a population of more than 7.5 million) from 2011 to 2017 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…The use of IFX treatment also showed a negative correlation with the rate of abdominal surgery in patients with AOP. This veri ed the conclusion that the increased use of biologics is positively correlated with a reduced need for abdominal surgery [26]. Furthermore, we observed that the time from the onset of PD to the diagnosis of PCD and the time from the diagnosis of PCD to the rst use of IFX were longer in the adult-onset cohort.…”
Section: Discussionsupporting
confidence: 82%
“…The use of IFX treatment also showed a negative correlation with the rate of abdominal surgery in patients with AOP. This veri ed the conclusion that the increased use of biologics is positively correlated with a reduced need for abdominal surgery [26]. Furthermore, we observed that the time from the onset of PD to the diagnosis of PCD and the time from the diagnosis of PCD to the rst use of IFX were longer in the adult-onset cohort.…”
Section: Discussionsupporting
confidence: 82%
“…As shown in our previous study [ 31 , 32 ], relative risk of overall hospitalization increased when compared with 2011, CD-related hospitalization rates slightly decreased (being statically significant in 2016 and 2017) and surgery and ostomies tend to decrease but not significantly. Regarding drugs, biological drugs increased (being statically significant over the period), immunosuppressant’s remained stable and salicylates and systemic corticosteroids significantly decreased (being statically significant between 2013 and 2017) ( Figure 2 , Supplementary Table 5 ).…”
Section: Resultssupporting
confidence: 52%
“…Data on the prevalence, incidence and mortality on CD and demographical variables have been described in detail in previous articles [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel disease (IBD), either Crohn’s disease (CD) or ulcerative colitis (UC), is a chronic, progressive, and life‐long condition that affects a large number of people in our country. 1 , 2 Lifetime medical costs associated with IBD care are comparable to those of other severe chronic diseases such as diabetes mellitus or cancer. 3 IBD is typically managed by gastroenterologists in collaboration with other healthcare specialities.…”
Section: Introductionmentioning
confidence: 99%